A Gut Feeling about GABA: Focus on GABAB Receptors - Hyland, Niall P.; Cryan, John F. (Frontiers in Pharmacology, 2010)
Gamma-Aminobutyric acid (GABA) is the main inhibitory neurotransmitter in the body and hence GABA-mediated neurotransmission regulates many physiological functions, including those in the gastrointestinal (GI) tract. GABA is located throughout the GI tract and is found in enteric nerves as well as in endocrine-like cells, implicating GABA as both a neurotransmitter and an endocrine mediator influencing GI function. GABA mediates its effects via GABA receptors which are either ionotropic GABAA or metabotropic GABAB. The latter which respond to the agonist baclofen have been least characterised, however accumulating data suggest that they play a key role in GI function in health and disease. Like GABA, GABAB receptors have been detected throughout the gut of several species in the enteric nervous system, muscle and epithelial layers as well as on endocrine-like cells. Such widespread distribution of this metabotropic GABA receptor is consistent with its significant modulatory role over intestinal motility, gastric emptying and acid secretion, transient lower esophageal sphincter relaxation and visceral sensation of painful colonic stimuli. More intriguing findings, the mechanisms underlying which have yet to be determined, suggest GABAB receptors inhibit GI carcinogenesis and tumour growth. Therefore, the diversity of GI functions regulated by GABAB receptors makes it a potentially useful target in the treatment of several GI disorders. In light of the development of novel compounds such as peripherally acting GABAB receptor agonists, positive allosteric modulators of the GABAB receptor and GABA producing enteric bacteria, we review and summarize current knowledge on the function of GABAB receptors within the GI tract.